2017
DOI: 10.5380/rf.v47i3.50222
|View full text |Cite
|
Sign up to set email alerts
|

Atividade Alelopática De Espécies Invasoras Sobre a Germinação E O Desenvolvimento Inicial De Arbórea Nativa

Abstract: ResumoPlantas invasoras surgem durante a sucessão ecológica e se desenvolvem juntamente com arbóreas nativas. A convivência entre essas espécies pode ser influenciada por vários fatores, como a alelopatia, definida como o conjunto de alterações diretas ou indiretas, que uma planta exerce sobre outra. Assim o objetivo do trabalho foi identificar a existência da ação alelopática na germinação das sementes e a possível interferência no crescimento inicial de plântulas de P. rigida quando submetidas aos extratos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Aggressive characteristics of D. teres and M. hirsutissima are known and stand out when they are present in high intense pastures, preferably on sandy soils (Lorenzi, 2008), being able to completely dominate the established pasture. Moreover, these weeds aggressive characteristics can compromise the native tree initial growing (Hartmann, Fortes, Cassol, Valmorbida, & Mendonça, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive characteristics of D. teres and M. hirsutissima are known and stand out when they are present in high intense pastures, preferably on sandy soils (Lorenzi, 2008), being able to completely dominate the established pasture. Moreover, these weeds aggressive characteristics can compromise the native tree initial growing (Hartmann, Fortes, Cassol, Valmorbida, & Mendonça, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Positive results found for A. urundeuva and C. pyramidale demonstrated that some of the native species tested tolerate low extract concentrations, which allows us to infer that the presence of fresh leaves of A. indica in the field does not interfere with the germination of those species in a negative way. Hartmann et al (2017) [30] also reported a positive effect on seedling growth for the native species Parapiptadenia rigida (Benth.) Brenan when submitted to leaf extracts made from the exotic Megathyrsus maximus (Jacq.)…”
Section: Radicle Lengthmentioning
confidence: 95%
“…LP Queiroz, and Mimosa caesalpiniifolia Benth. ; Hartmann et al (2017) [30] observed the effect of the exotic Brachiaria brizantha Stapf (palisade grass) on Parapiptadenia rigida (Benth.) Brenan; lastly, Costa and Freire (2018) [31] investigated the extract effect of the exotic Prosopis juliflora (Sw.) DC.…”
Section: Introductionmentioning
confidence: 99%
“…Os metabólitos secundários são intitulados de aleloquímicos e estão presentes em diferentes órgãos das plantas e podem ser liberados por diferentes vias como pela lixiviação dos tecidos, dissolução em água, volatilização de compostos aromáticos, portanto, induzindo direta ou indiretamente nas interações entre as plantas (ZENG et al, 2010;HARTMANN, 2017). Na natureza este processo é chamado de alelopatia, tendo como principal função minimizar ou acabar com a competição por recursos, entre eles a luminosidade e nutrientes (RICE, 1984;FERREIRA & BORGHETTI, 2004;FUJII & HIRADATE, 2007;OLIVEIRA et al, 2014).…”
Section: Introductionunclassified